A simulation framework to ensure data consistency in sensor networks - Shah, Nikhil Jeevanlal (Kansas State University, 2008)
The objective of this project is to address the problem of data consistency in sensor network applications. An application may involve data being gathered from several sources to be delivered to multiple sinks, resulting in multiple data streams with several sources and sinks for each stream. There may be several inter-stream constraints to be satisfied in order to ensure data consistency. In this report, we model this problem as that of variable sharing between the components in an application, and propose a framework for implementing variable sharing in a distributed sensor network. In this framework, we define the notion of variable sharing in component based systems. We allow the application designer to specify data consistency constraints in an application. Given an application, we implement a tool to identify various types of shared variables in an application. Given the shared variables and the data consistency constraints, we provide an infrastructure to implement the shared variables. This infrastructure has tools to synthesize the code to be deployed on each of the nodes in the physical topology. The infrastructure has been built for the TinyOS platform. We have evaluated the framework using several examples using the TOSSIM simulator.
Keywords: Sensor Networks; Data Consistency; Atomic Consistency; Causal Consistency; Computer Science (0984)